2012
DOI: 10.1186/ar3801
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and dynamic gait compensations resulting from knee instability in a rat model of osteoarthritis

Abstract: IntroductionOsteoarthritis (OA) results in pain and disability; however, preclinical OA models often focus on joint-level changes. Gait analysis is one method used to evaluate both preclinical OA models and OA patients. The objective of this study is to describe spatiotemporal and ground reaction force changes in a rat medial meniscus transection (MMT) model of knee OA and to compare these gait measures with assays of weight bearing and tactile allodynia.MethodsSixteen rats were used in the study. The medial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 51 publications
(68 reference statements)
4
94
1
Order By: Relevance
“…When challenged by CFA under chronic conditions, rats can transfer their bodyweight from the irritated paw to the healthy counterpart [25,26] . Therefore, the weight difference between the paw pair reflects the severity of pain.…”
Section: Anti-nociceptive Effect Of Qo58-lysine On Cfa-induced Inflammentioning
confidence: 99%
“…When challenged by CFA under chronic conditions, rats can transfer their bodyweight from the irritated paw to the healthy counterpart [25,26] . Therefore, the weight difference between the paw pair reflects the severity of pain.…”
Section: Anti-nociceptive Effect Of Qo58-lysine On Cfa-induced Inflammentioning
confidence: 99%
“…The magnitude at which the animal withdraws its foot is reported as the paw withdrawal threshold, and a lower paw withdrawal threshold is taken to represent increased sensitivity and neuropathic pain in the distal limb. Decreased paw withdrawal thresholds have been reported in a number of rat OA models including MMT (42,43), partial medial meniscectomy (44), and monosodium iodoacetate injection (44). When the filament is applied, however, it has been reported that filaments with stiffness greater than 16 g may lift the rat's foot (44).…”
Section: Pain Function and Gaitmentioning
confidence: 99%
“…There is currently no standard method of gait analysis for use in animal OA models. Published methods have included scoring based on apparent lameness (40), measurement of stride length and limb rotation from inked paw prints in rats (48), measurement of dynamic force application using a pressure-sensitive walkway (42,46), and fluoroscopic measurements of hind limb motion (47). In larger animals, gait and functionality measures such as kinematic marker analysis, ground reaction force measurements, and observational gait assessment have been applied to study OA-related changes for conditions including dog hip OA (49), lameness in horses (50), and postsurgical sheep knee OA (51).…”
Section: Pain Function and Gaitmentioning
confidence: 99%
“…Signifi cant differences in serum cytokines were not identifi ed between groups. Histological lesions were signifi cantly worse in MMT/MCLT than MCLT [ 70 ]. Thus, MMT/MCLT produces very distinctive functional and histological defi ciencies that MCLT alone does not.…”
Section: Medial Meniscal Tear/medial Collateral Ligament Transection mentioning
confidence: 88%
“…The additional effect of MMT compared to MCLT alone has been recently investigated in Lewis rats followed for 28 days postoperatively [ 70 ]. MMT/MCLT limbs had increased mechanical allodynia compared to unoperated in the same animal, but compared to control animals, there was only a trend to increased mechanical allodynia in MMT/MCLT groups, and no difference between surgical groups.…”
Section: Medial Meniscal Tear/medial Collateral Ligament Transection mentioning
confidence: 97%